2020
DOI: 10.1016/j.cej.2019.123648
|View full text |Cite
|
Sign up to set email alerts
|

The effect of H2O on formation mechanism of arsenic oxide during arsenopyrite oxidation: Experimental and theoretical analysis

Abstract: The effect of H2O on arsenic release behavior was investigated via experiment and firstprinciples density functional theory (DFT). The experimental results show that sulfide-bound arsenic is the main form present in coal, and that H2O has a positive influence on the release of arsenic during coal combustion. Furthermore, DFT calculations were performed to investigate the mechanism for H2O influence on arsenic oxidation. Thermodynamic and kinetic analyses were also conducted to study the influence of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
3
16
1
Order By: Relevance
“…To further understand the mechanisms of NO oxidation and NO 2 reduction reactions, density functional theory (DFT) calculations were used as a powerful method for obtaining accurate chemical reaction pathways, molecular structures, and energy profiles as well as kinetic and thermodynamic parameters. In terms of DFT calculations, Li et al determined the mechanisms of the NO oxidation reaction when it is absorbed on a TiO 2 surface and showed that the O-containing groups can serve as an effective reactant to oxidize NO molecules, in agreement with the work of Razavi et al Similar studies have been conducted using DFT calculations on the NOx reduction reaction on different material surfaces, such as carbon, metal catalysts, or others. Jiao et al carried out a DFT study on the NO reduction reaction via a char edge model, and the influence of CO on the NO reduction reaction was also taken into account.…”
Section: Introductionmentioning
confidence: 61%
“…To further understand the mechanisms of NO oxidation and NO 2 reduction reactions, density functional theory (DFT) calculations were used as a powerful method for obtaining accurate chemical reaction pathways, molecular structures, and energy profiles as well as kinetic and thermodynamic parameters. In terms of DFT calculations, Li et al determined the mechanisms of the NO oxidation reaction when it is absorbed on a TiO 2 surface and showed that the O-containing groups can serve as an effective reactant to oxidize NO molecules, in agreement with the work of Razavi et al Similar studies have been conducted using DFT calculations on the NOx reduction reaction on different material surfaces, such as carbon, metal catalysts, or others. Jiao et al carried out a DFT study on the NO reduction reaction via a char edge model, and the influence of CO on the NO reduction reaction was also taken into account.…”
Section: Introductionmentioning
confidence: 61%
“…An adsorption with E ads < 0.4 eV is regarded as a physical adsorption, and E ads > 0.5 eV is regarded as a chemical adsorption . The Gibbs free energy change of an adsorption process, Δ G ads , was calculated by eqs – where G is the Gibbs free energy, T is the thermodynamic temperature (K), S is the entropy, and R is the gas constant.…”
Section: Methodsmentioning
confidence: 99%
“…Figure S3 displays the PDOS of bonded O and As atoms on the (101) 42 Additionally, these numbers were smaller than the value of −123.46 kJ/mol, which was obtained for pyrite (surface doping an As atom) by using the GGA + PBE method. 38 This difference might be S3). Table S3 also demonstrates that H 2 O molecules can enhance the dissociation of the O−O bond on the arsenopyrite/pyrite surface.…”
Section: Oxidation Behavior Of Omentioning
confidence: 97%
“…22,34,38−41 The (001) surface of arsenopyrite and pyrite exhibits high stability and the crystal model can be established along this plane for the adsorption and oxidation mechanisms of O 2 /O 2 + H 2 O. 38,39 The oxidation of the FeAsS and the FeS 2 interface is also greatly enhanced in the presence of H 2 O. 34,38 The pyrite surface oxidizes as a result of the multistep complex reactions between the surface and the adsorbed O 2 and water molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation